PENGGUNAAN INTERNATIONAL CENTRE FOR INTEGRATED MOUNTAIN DEVELOPMENT (ICIMOD) OLEH BHUTAN UNTUK MENCAPAI KEPENTINGAN NASIONAL TERKAIT ECOTOURISM - Ernayanti, Ni Komang; Sushanti, Sukma; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
Bhutan is a small landlocked developing country which is located in the South Asia region. Bhutan relies on ecotourism policies which applies High Value Low Volume principle and forms International Center for Integrated Mountain Development (ICIMOD) as a forum for international cooperation. This research used qualitative descriptive methods to analyze the issues. This issue discussed by answering question to how Bhutan uses ICIMOD as an agenda setting to achieve its national interests related to ecotourism. The data in this research were analyzed through power in international organizations from the perspective of defensive realism that focuses on agenda setting in international relations. This research also describes how Bhutan uses ICIMOD as a forum for achieving Bhutan's interests in the field of ecotourism and as one of Bhutan's national security projections that have a positive impact on Bhutan's development. Keywords: Bhutan, Ecotourism, ICIMOD, Power in International Organizations, Agenda Setting